Progestins for pituitary suppression during ovarian stimulation in artificial reproductive technology (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Progestins can suppress endogenous luteinizing hormone secretion from the pituitary gland. Progestins can be used orally and are less expensive than gonadotrophin-releasing hormone (GnRH) analogs. However, early endometrial exposure to progestin precludes fresh embryo transfer (ET), but the emergence of vitrification for oocyte cryopreservation cycles allows more opportunities for using progestins for pituitary suppression.Objective: To assess the mechanism of pituitary suppression by progestins, the effectiveness of progestins compared with GnRH analogs, the effect of progestins on oocyte and embryo developmental potential and euploidy status, and the cost-effectiveness of progestin-primed stimulation. Methods: A literature search using the keywords “multiple waves of antral ovarian follicular development,  In Vitro Fertilization, Ovarian stimulation ” was performed in the PubMed database.Results: The duration of stimulation, gonadotrophin consumption, and oocyte yield were similar in progestins and GnRH analogs. However, progestins were associated with significantly lower gonadotrophin consumption than their analogs. Overall, live birth and clinical pregnancy rates per ET were similar to those of progestins and GnRH analogs. Studies comparing medroxyprogesterone acetate, dydrogesterone, and micronized progesterone suggest similar ovarian responses and pregnancy outcomes. The euploidy status of embryos and obstetric and neonatal outcomes from progestin-primed cycles are similar to those of embryos from conventional stimulation cycles. Despite the lower cost of progestins than GnRH analogs, the mandatory cryopreservation of all embryos followed by a deferred transfer may increase the cost per live birth with progestins compared with an artificial reproductive technology cycle culminating in a fresh ET.Conclusion: Progestins present an effective option for women who do not contemplate a fresh ET, e.g., fertility preservation, anticipated hyper responders, preimplantation genetic testing, oocyte donors, and double stimulation cycles.